Acute Abdomen and Perforated Bowel with a Rare Pathology: Nonfamilial Visceral Myopathy. (8th December 2011) - Burcharth, Jakob; Olsen, Caroline; Rosenberg, Jacob
Abstract : Visceral myopathy is a rare chronic disease affecting the peristalsis of the bowel causing intermittent pseudoobstruction. We report an atypical case of an eighty-nine-year-old woman with no prior history of abdominal illness who was admitted to our hospital with 2 days of increasing nausea, abdominal distension, and abdominal pain. On arrival at the hospital, she was critically ill. Abdominal X-ray showed distended loops of the colon and liquid levels resembling colonic obstruction. A subsequent abdominal CT scan confirmed the colonic obstruction. A suspicion of sigmoid volvulus was raised, that is why a barium enema was performed but no lower colonic obstruction could be confirmed. Acute laparotomy showed perforated cecum without intestinal obstruction. Postoperatively, the patient became septic which was fatal for the patient. Pathology gave the diagnosis visceral myopathy. It is very difficult to make the diagnosis clinically and radiologically since visceral myopathy mimics other more common gastrointestinal diseases. It is important to consider visceral myopathy as a possible diagnosis in cases with recurrent episodes of abdominal pain, vomiting, and abdominal distension, but without actual intestinal obstruction.